2018
DOI: 10.1113/jp275083
|View full text |Cite
|
Sign up to set email alerts
|

Resurgent sodium current promotes action potential firing in the avian auditory brainstem

Abstract: Key points Auditory brainstem neurons of all vertebrates fire phase‐locked action potentials (APs) at high rates with remarkable fidelity, a process controlled by specialized anatomical and biophysical properties.This is especially true in the avian nucleus magnocellularis (NM) – the analogue of the mammalian anteroventral cochlear nucleus.In addition to high voltage‐activated potassium (KHVA) channels, we report, using whole cell physiology and modelling, that resurgent sodium current (I NaR) of sodium channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(51 citation statements)
references
References 73 publications
(198 reference statements)
3
47
0
Order By: Relevance
“…Resurgent currents appear when neurons are repolarized after prolonged depolarization. They are reported to promote spontaneous firing and high‐frequency firing of inhibitory neurons and may be a promising antiepileptic therapeutic target . A computer model that includes the unique activation features of resurgent currents is still to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Resurgent currents appear when neurons are repolarized after prolonged depolarization. They are reported to promote spontaneous firing and high‐frequency firing of inhibitory neurons and may be a promising antiepileptic therapeutic target . A computer model that includes the unique activation features of resurgent currents is still to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation of NMc electrical activity were performed in NEURON 7.1 ( Hines and Carnevale, 1997 ) by employing a single-compartment model ( Table 2 ). The NMc model was based on our NM model previously described and all ion currents were modeled using the same formalism ( Tables 2 , 3 , Hong et al, 2017 ; Lu et al, 2017 ). Briefly, this model contains currents mediated by low- and high-voltage activated potassium (K + LV A and K + HV A , respectively) channels, Na V , and passive leak channels.…”
Section: Methodsmentioning
confidence: 99%
“… Kuba and Ohmori (2009) also showed larger Na V current amplitude and higher Na V channel density, as indicated by stronger immunoreactivity, toward lower-frequency NM. Furthermore, we showed that Na V 1.6-channel subtype is expressed in mid- to high-frequency NM and carry robust resurgent Na V current ( I NaR ) ( Hong et al, 2017 ). I NaR is a prevalent property conserved in auditory structures of both avians and mammals and plays an important role in high-frequency AP firing of peripheral and brainstem neurons ( Leao K.E.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations